An analysis of farm support measures in the Republic of Moldova - Judith Möllers; Thomas Herzfeld; Lucia Batereanu; Arjola Arapi-Gjini (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2022)
In the Republic of Moldova, agricultural policies aim to increase the compettveness of its farming sector, ensure the sustainable management of its natural resources and improve the living standards in rural areas. The state is an important player, allocatng fnancial resources for supportng agriculture and carrying out investment projects in this feld. A post-investment subsidy program incentvises agricultural producers to modernise their farms and producton. Farmers who have made investments in developing producton and post-harvest infrastructure could beneft from subsidies for these investments and fnancial resources allocated by the Agency for Interventon and Payments in Agriculture. However, it is not clear how benefcial these subsidies are for agricultural producers and whether the goals formulated by policies are met. A critcal challenge of policy assessment is the lack of regular surveys gathering farm-level data in Moldova. Another challenge is that the impact of some investments can only be quantfed with a delay of several years. This report results from an impact assessment study analysing the efectveness of existng policy measures. A survey of 800 farms was carried out to realise this assessment, which provided informaton about the actvity and investments made over several years. The team of researchers analysed the collected data to evaluate the policy measures covered by the survey. The study highlights essental facilitators and barriers to the farms' agricultural investment and business actvity. The impact assessment underlined that the investment subsidies had measurable positve efects on labour, farm producton and economic success. At the same tme, it indicated directons for improving and rebalancing policy instruments to increase the compettveness and sustainability of the agricultural sector of the Republic of Moldova.
urn:nbn:de:gbv:3:2-913953
Keywords: 330; Moldova; farm subsidies; agricultural policies; impact assessment